THE INTRINSIC ELEMENTS AND MOTIVES FOR TEEN SUICIDE DEPICTED IN THE NOVEL ENTITLED THIRTEEN REASONS WHY BY JAY ASHER 2007 - Ayu Rahmatiah, Hani; Simaibang, Baginda; Puspita Sari, Artanti (Wiralodra English Journal, 2021)
Literature is one of the tools used by humans to depict social phenomenon. Since centuries ago, there are a lot of literary works have brought up suicide into the topics. Today, this topic is still becoming a thing in popular novels. One of the most popular is Thirteen Reasons Why by Jay Asher. Data are collected by using the novel. Data were analyzed by detailing intrinsic elements, motives for teen suicide, and the theoretical implications for English Language Teaching. The findings of this research explained some interesting things about this novel. First, it is about how Jay Asher presents each element in this novel not only visually, but also how the elements are perceived by the characters. Jay uniquely presents two narrations from Hannah & Clay back and forth throughout the novel, which makes this novel very interesting. Second, there are 7 from 10 items on IMSA found in Hannah's statements that scientifically support her actions to end her life. Third, this novel could be used as a tool for teachers to teach about empathy, mental health, and suicide prevention in High Schools.